Drivers toward social entrepreneurs engagement in Poland: An institutional approach - Agnieszka Pacut (Administrative Sciences, 2020)
The aim of this study is to identify the factors that influence the involvement of individuals in social entrepreneurship in Poland from an institutional economics perspective. The research is based on exploratory data analysis using qualitative data covering 22 interviews with social entrepreneurs and 10 representatives of stakeholders from Poland as well as observations and secondary data. By employing an inductive approach and a case study methodology, it can be stated that involvement of social entrepreneurs is stimulated by a complex set of factors. Moreover, the results show the importance of the institutional environment for social enterprises in Poland, including the impact of formal and informal institutions on their development. The findings contribute to enhancing the knowledge on factors determining the establishment and development of social enterprises in Poland given the institutional economics perspective.
Keywords: 350; social enterprise; social entrepreneurship; social entrepreneur; factors; institutional environment; Poland